(untitled) (Research, Society and Development, 2022)
The increase in the consumption of medicines around the world has generated several studies on the impacts caused by the inappropriate disposal of waste containing the active ingredients of medicines in the environment. After being ingested, these drugs are excreted in the form of other compounds in domestic sewage, many of which are still persistent in the environment and generate physiological changes in aquatic organisms. Due to population growth and excessive consumption, the anti-inflammatory known as diclofenac sodium is among the main drugs found in Brazilian surface waters, in concentrations in the range of micrograms per liter (µg.L-1). This work aimed to study the biomolecular changes that diclofenac can cause in fish of the Brycon opalinus species, using the Fourier Transform Infrared Spectroscopy (FTIR) technique coupled with chemometric methods, principal component analysis (PCA) and hierarchical cluster analysis (HCA). Two different concentrations of diclofenac sodium plus the control were studied. The organ selected for this study were the gills. PCA and HCA results showed discrimination between the control and treated spectra. The quantitative analysis, by calculating the areas of the bands of lipids, proteins and carbohydrates, showed changes in these biomolecules, with proteins and carbohydrates being more sensitive to exposure to diclofenac. The results of the deconvolution and curve fitting showed a decrease in the disordered structure and an increase in β sheet of the protein secondary structure for the exposure of 4.4 µg.L-1 of diclofenac.